An Investigation of Proteolytic, Lipolytic Activity and Biofilm Formation by Psychrotrophic Bacteria Isolated from Buffalo Milk - Bogo, Marciele; Lauer Cruz, Karine; Gonzalez Revello, Ãlvaro; Frazzon, Ana Paula Guedes; de Souza da Motta, Amanda (Journal of Buffalo Science, 2017)
The aim of this study was to investigate the enzymatic activity of 21 bacteria isolated from refrigerated raw buffalo milk, as well as to evaluate the production of biofilm by these bacteria. Proteolytic, lipolytic and lecithinase activity, as well as the production of exopolysaccharides were evaluated at different temperatures. For all of the psychrotrophic bacteria, biofilm formation on microtiter plates was evaluated at different temperatures and in the presence of residual buffalo and bovine milk. All cultures showed a proteolytic profile while 9 cultures showed lipase activity. Lecithinase production was found in 7 of the evaluated psychrotrophic bacteria. The ability to produce exopolysaccharides was found in 12 bacteria. Of the 21 bacterial isolates, 16 were biofilm producers at 7°C. At 23°C, 20 isolates were found to be biofilm producers. At a temperature of 37°C, biofilm formation by 17 isolates was weak. In the presence of residual buffalo milk, 7 were biofilm producers, while 16 bacteria produced biofilm in residual bovine milk. The results of this study show that many isolates of psychrotrophic bacteria from raw buffalo milk have the potential to produce extracellular enzymes as well as biofilm. This deserves special attention when considering the best practices to recommend during the collection of raw milk in establishments which process milk.